n = 2 ∑ ∞ k = 1 ∑ ∞ ( k k + n ) ( − 1 ) n
If the above summation equals S , what is the value of ⌊ 1 0 0 0 0 S ⌋ ?
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Sir this is really beautiful Problem.Since Initially I thought It needs advanced calculus , but then It convert into interesting telescopic series , I really Love in solving such type sequences and series . Thanks for Posting such problems , and also I want to request you to Please Post such more sequence and series problems. I always waiting for such problems.
Also Sir One More request , It's long time you have not Posted Geometry Problems Like as your famous "Tight Fits" . We all are eagerly waiting for them , So sir Please post such more. Thanks Sir !
Log in to reply
Thanks, Deepanshu. I'll try and come up with a geometry problem next. :)
Beta function can also be used!
Log in to reply
Seems like Beta function is your fav ! You always have a Beta function solution ready :P
Wow that's magnificent!
It's totally unexpected to transform that series into a telescoping one! Cheers :)
Problem Loading...
Note Loading...
Set Loading...
First we'll look at k = 1 ∑ ∞ ( k k + n ) 1 = k = 1 ∑ ∞ ( n k + n ) 1 =
k = 1 ∑ ∞ n ! ( k + 1 ) ( k + 2 ) ⋯ ( k + n ) 1 =
n ! k = 1 ∑ ∞ ( k + 1 ) ( k + 2 ) ⋯ ( k + n ) 1 =
n − 1 n ! k = 1 ∑ ∞ ( ( k + 1 ) ( k + 2 ) ⋯ ( k + n − 1 ) 1 − ( k + 2 ) ( k + 3 ) ⋯ ( k + n ) 1 ) =
n − 1 n ! ( 2 ∗ 3 ⋯ n 1 − 3 ∗ 4 ⋯ ( n + 1 ) 1 + 3 ∗ 4 ⋯ ( n + 1 ) 1 −
4 ∗ 5 ⋯ ( n + 2 ) 1 + 4 ∗ 5 ⋯ ( n + 2 ) 1 − + ⋯ ) =
n − 1 n ! ∗ n ! 1 = n − 1 1 ,
where in the next to last step we have formed a telescoping series with all the terms in the brackets canceling out in pairs except the first term. So now
S = n = 2 ∑ ∞ n − 1 ( − 1 ) n = 1 − 2 1 + 3 1 − 4 1 + − ⋯ = ln ( 2 ) = 0 . 6 9 3 1 4 7 1 8 1 . . . . .
Thus ⌊ 1 0 0 0 0 ∗ S ⌋ = 6 9 3 1 .